Agricultural Economics and the Transformation Toward Sustainable Agri-Food Systems - Matin Qaim; Martin C. Parlasca (Agricultural Economics, 2025)
Agri-food systems around the world are facing a sustainability crisis. Addressing the many interconnected issues requires fundamental transformations, moving beyond incremental improvements of various details toward broader and more profound systemic change. In this article, which is also the introduction to the ICAE 2024 Special Issue, we explore the role of our agricultural economics profession in shaping these transformation processes, examining how our discipline contributes to understanding agri-food system dynamics and identifying opportunities to enhance sustainability and resilience. We argue that agricultural economists can and should play a more central role in international agri-food systems research and policy initiatives by integrating multiple sustainability goals and metrics with rigorous economic analysis. Interdisciplinary cooperation with colleagues in agronomy, nutrition, environmental sciences, social and political sciences, and other relevant fields is necessary, as is the further development and use of data-driven approaches. However, equally important is maintaining strong theoretical foundations to develop hypotheses and understand behavioral mechanisms. Close exchange with nonacademic stakeholders at all system levels is key for policy relevance. We also provide an overview of the plenary papers presented at ICAE 2024 on various facets of agri-food system transformation and sustainable development.
Keywords: 330; Food systems; planetary boundaries; malnutrition; climate change; interdisciplinary research